Analisis Kesulitan Belajar Perubahan Wujud Benda Pada Siswa Sekolah Dasar (Jurnal Sekolah Dasar, 2025)
This study aims to develop valid and reliable questions, identify the level of learning difficulties based on the material of changes in the form of objects, and describe questions with easy and difficult categories. This research uses quantitative methods with data collection through tests. The research subjects were 17 students and an teacher. The results showed that 70% of the questions were valid with a Cronbach's Alpha reliability value of 0.77, indicating good instrument consistency. The difficulty level of the questions was dominated by the easy category (60%), while the highest student learning difficulty (70.58%) occurred in the indicator explaining the phenomenon of changes in the form of objects, especially the condensation process. The average student score was 68.82, which was below the Minimum Completion Criteria (75-78). The learning difficulty factor is related to students' lack of understanding of abstract concepts. Therefore, it is recommended that teachers use interactive learning methods and innovative media to improve student understanding. This research provides recommendations for the development of learning difficulties analysis-based science learning in primary schools, especially in supporting teachers to create effective learning strategies and improve student achievement.